Da norma mais favorável ao trabalhador à norma mais favorável ao trabalho: o conflito de leis trabalhistas no espaço e uma análise consequencial da tomada de decisão no teletrabalho transnacional - Bitencourt, Manoela de (2020)
Globalization and new technologies are changing the world of work. The use of technology for the provision of services allows the worker to have greater autonomy in the conduct of his activities, to work at a distance, and in another country. In addition, a new generation of workers, called Millennials, until 2025, will make up 75% of the active labor force. This generation's main characteristic is to have more freedom in the management of their work activities. Thus, the use of technology and the workforce composed by this new generation lead to a reformulation of the subordination requirement. In this sense, a new labor law appears, with new forms of social contracts and jobs, supported by a new reality, with new technological devices. Such a context leads to a flexible employment relationship, in which time and work space are relativized. For this reason, a new typology is proposed that provides protection to the self-employed worker and in which the protections in employment relationships are measured, according to the employee's needs. In addition, there is the possibility of a new type of service provision, carried out remotely, and in another country, called transnational teleworking. In this context, it is possible for a conflict of labor laws to occur in space, which is why the present work pertains to the law applicable to that contract, in order to regulate the legal situation, when not provided for in the labor agreement. Private international law elects connecting elements for resolving the dispute, while labor law also elects its connecting criterion. Among others, it stands out the criterion of the worker's nationality, the law of the country in which the services are provided, the law of the place where the company maintains its headquarters, the law of the place of hiring, the law of the country where the company has registered the its server (because it is about providing services in cyberspace) and the principle of the most favorable norm. In the present work, the hypothetical-deductive approach method is applied. Regarding the investigation, the research uses the methodological procedure essentially monographic and historical and the structuralist and functionalist procedure. The systematic method is also used, and the research technique, as far as nature is concerned, is qualitative. As for its purpose, it is descriptive. And, as for the object, it is bibliographic. With regard to the connecting element that must be taken into account by the interpreter in order to make a decision in the event of a conflict of labor laws in transnational teleworking, the present research chooses the utilitarian criterion. In addition, the consequences of the decision and the economic impact it has on the work context should guide the interpreter in choosing the law applicable to the specific case, implying that happiness and well-being are for the greatest possible number of people. It is concluded, with this study, that in face of the conflict of laws in the space, in the transnational telework, the norm to be applied must be the most favorable to the work, that is, to the worker, the company, the society and the other workers that may be involved in this decision, thus making it possible to enforce the collective fundamental rights of all those involved, the foundations of work and free enterprise and the guarantee of social justice.